International law and chemical, biological, radio-nuclear (CBRN) events : towards an all-hazards approach - De Guttry, Andrea; Frulli, Micaela; Casolari, Federico; Poli, Ludovica, 1978- (Brill Nijhoff, 2022)
"The volume investigates to what extent the international and European Union legal frameworks applicable to Chemical, Biological and Radio-Nuclear (CBRN) events are adequate to face current challenges. It is innovative in many aspects: it adopts an all-hazard approach to CBRN risks, focusing on events of intentional, accidental and natural origin; it explores international obligations according to the four phases of the emergency cycle, including prevention, preparedness, response and recovery; and it covers horizontal issues such as protection of human rights, international environmental law, new technologies, the role of private actors, as well as enforcement mechanisms and remedies available to victims. The book thus offers a new way of looking at the applicable rules of international law in this field"--